2021 IEEE International Conference on Robotics and Automation (ICRA) 2021
DOI: 10.1109/icra48506.2021.9561184
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion and Control of a Friction-Driven Tripedal Robot

Abstract: This letter considers control of a radially symmetric tripedal friction-driven robot. The robot features 3 servo motors mounted on a 3-D printed chassis 7 cm from the center of mass and separated 120 degrees. These motors drive limbs, which impart frictional reactive forces on the body. Experimental observations performed on a uniform friction surface validated a mathematical model for robot motion. This model was used to create a gait map, which features instantaneous omni-directional control. We demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Several recent efforts have considered the development of radially symmetric robots. Our previous work describing the development of the tripedal test system used in this study showed that the radially symmetric arrangement is controllable using an omnidirectional gait map Hermes et al (2021). This prior effort also highlighted an advantage of being able to define arbitrary lead limbs for radially symmetric robots: sharp path curves can easily be followed.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Several recent efforts have considered the development of radially symmetric robots. Our previous work describing the development of the tripedal test system used in this study showed that the radially symmetric arrangement is controllable using an omnidirectional gait map Hermes et al (2021). This prior effort also highlighted an advantage of being able to define arbitrary lead limbs for radially symmetric robots: sharp path curves can easily be followed.…”
Section: Introductionmentioning
confidence: 78%
“…The ability to move along prescribed curves, rotate in place, and travel in a straight line establishes a framework for future motion planning efforts for radially-symmetric crawling robots. Using the models developed in this paper, we have successfully demonstrated path following for this robot using image-based feedback control Hermes et al (2021). The primary advantage of radial symmetries highlighted in this work is the omni-directional translation ability.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation